GRASSROOTS GOVERNANCE POLICIES, CAUSE AND CONSEQUENCES OF YOUTH UNEMPLOYMENT IN RURAL INDIA - Jayaprada Sahoo; Dr. Vadranam Suresh (Scholar Express Journal, 2021)
Employment and Unemployment is a two important debatable concept in the society unemployment is major threat in economic development in a nation, but the term unemployment is serious problem in across the globe. The unemployment problem found not only India but also some developed countries like, USA, New Zealand, Spain, etc., on the other hand, the learn of unemployment in Indian state serious problem in 21st century. Youth unemployment come off in modern Indian state Odisha, currently deliberate as a percentage of the parallel active labour force, only about 23 percent youth unemployment on average in the European state. Odisha is an agriculture-based society and maximum of people in rural area depends on agriculture and growth of population and poverty the unemployment problem increased day by day there are some problems to improve the unemployment in Odisha that lack of transport and communication facility and youth are educated but they do not have skill a particular field.
Keywords: Employment and Unemployment; Economic Development; Skill Works; Population